2017
DOI: 10.1177/1941738117747851
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Return to Cycling After Hip Arthroscopy for Femoroacetabular Impingement Syndrome

Abstract: Cyclists return to sport 97% of the time at an average of 4.5 months after hip arthroscopy for FAIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…13 We believe that labral repair is the gold standard for labral tear treatment, as studies have shown excellent outcomes and high rates of return to sport after labral repair. 19,24,31,33,34,40 However, in cases of irreparable, nonviable, or calcified labra, labral reconstruction has recently emerged as a viable procedure. Literature shows that in these cases, labral reconstruction can restore labral function and is preferred over debridement or excision.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…13 We believe that labral repair is the gold standard for labral tear treatment, as studies have shown excellent outcomes and high rates of return to sport after labral repair. 19,24,31,33,34,40 However, in cases of irreparable, nonviable, or calcified labra, labral reconstruction has recently emerged as a viable procedure. Literature shows that in these cases, labral reconstruction can restore labral function and is preferred over debridement or excision.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
“…Literature shows favorable VAS, patient satisfaction, and return to sport after labral repair. 4,19,31,33 Furthermore, labral reconstruction is among the most challenging procedures in hip arthroscopy, as evidenced by the handful of surgeons currently performing labral reconstructions. 18,35,36,44,46 This study has several strengths.…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
“…2,10,30 The arthroscopic approach further yields excellent outcomes for returning to activity and sport following surgery. 9,13,24,26,32 Cvetanovich et al 9 found that 89.2% of patients returned to activities at or above their preoperative participation levels at 2-year follow-up. Additionally, studies of outcomes after FAI treatment have begun to measure improvement based on the minimal clinically important difference (MCID) by evaluating change in pre- and postoperative patient-reported outcome (PRO) scores.…”
mentioning
confidence: 99%
“…Thus, hip arthroscopy possibly provides good clinical outcomes for cycling athlete with FAI. 2 There are similar reports of coxarthrosis caused by unicycling. 3,4 However, no epidemiological studies on the relationship between unicycling and groin pain are available in the literature.…”
Section: Introductionmentioning
confidence: 73%
“…In addition, it should be considered that in unicyclists with groin pain, they need to take rest period or reduce time on training. Journal of Orthopaedic Surgery 28 (2)…”
Section: Resultsmentioning
confidence: 99%